(untitled) (American Journal of Pedagogical and Educational Research, 2023)
This is the study of the means of speech etiquette in the Uzbek language - affixes, lexical units, stable combinations in the light of modern paradigms of linguistics and the necessary means of forming a culture of communication. determined the pedagogical and psychological criteria.